Pengaruh Frekuensi dan Jenis Penggunaan Internet Terhadap Kohesi Keluarga Melalui Mediasi Waktu Keluarga Dan Konflik Keluarga - widiyanto, keyarsha; Ikhsan Fuady, S.P., M.Si; Ikhsan Fuady, S.P., M.Si3 (AT-TAWASUL, 2025)
ABSTRACT The development of the internet impacts family dynamics through changes in interaction patterns, family time, and family conflict. This study aims to analyze the effect of internet usage frequency and type on family cohesion, mediated by family time and family conflict. Using a quantitative approach with a survey design, data were collected from 100 family respondents with adolescents aged 13–20 years through questionnaires and analyzed using the PLS-SEM method. The findings reveal that the frequency of internet use negatively correlates with family cohesion due to increased conflict, whereas internet use for educational purposes positively influences family cohesion through family time mediation. This study highlights that online activities, such as gaming or social media, tend to escalate family conflicts, while educational activities enhance family cohesion. Additionally, family time serves as a crucial mediator in mitigating the negative effects of internet usage. With proper regulation, the internet can become a tool for fostering family harmony. This research provides significant implications for families and policymakers to maximize the positive potential of technology while minimizing its risks of family conflicts caused by internet use.